19. THE ROLE OF CIVIL AVIATION IN THE DEVELOPMENT OF COUNTRIES - Salimov Bakhriddin Lutfullaevich. Normuminov Asilbek Akbarovich (Innovative technologies in construction Scientific Journal, 2023)
The article provides information about the emergence of air transport and its penetration into Central Asia. It was also analyzed that during the years of independence, unprecedented works were carried out in the field as a result of the development of air transport along with all types of transport in Uzbekistan, aimed at improving the economy and technology, as a result of optimally effective management of resources.